Time, History, and Political Thought - Robertson, John (Cambridge University Press, 2023)
Explores the multiple ways in which different conceptions of time and history have been used to understand politics since late antiquity, showing that no conception of politics has dispensed altogether with time, and many have explicitly sought legitimacy in association with forms of history